2003
DOI: 10.1111/j.1944-8287.2003.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Agglomeration and Development: A Survey of Spatial Economic Issues in East Asia and a Statistical Analysis of Chinese Regions

Abstract: In this article, we explore the issue of industrial agglomeration and its relationship to economic development and growth in the less‐developed countries of East Asia. We present theoretical arguments and secondary empirical evidence as to why we should have strong expectations about finding a positive relationship between agglomeration and economic performance. We also review evidence from the literature on the roles of formal and informal institutions in East Asian regional economic systems. We then focus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
192
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(212 citation statements)
references
References 73 publications
5
192
1
3
Order By: Relevance
“…The barycenter of each crop from 1981 to 2012 was calculated using Equation (1). As Figures 3 and 4 show, from 1981 to 2012, overall, the barycenter of cereals moved to the northeast from 113.6°E, 32.3°N in 1981 to 114.4°E, 35.5°N in 2012, although the specific path was more complex.…”
Section: The Path Of Each Crop's Barycentermentioning
confidence: 99%
See 3 more Smart Citations
“…The barycenter of each crop from 1981 to 2012 was calculated using Equation (1). As Figures 3 and 4 show, from 1981 to 2012, overall, the barycenter of cereals moved to the northeast from 113.6°E, 32.3°N in 1981 to 114.4°E, 35.5°N in 2012, although the specific path was more complex.…”
Section: The Path Of Each Crop's Barycentermentioning
confidence: 99%
“…New classical economics considers that industrial agglomeration is determined by the division of labor in the economy and transaction efficiency, and it is based on an infra-marginal analysis of the division of labor [10]. Fan and Scott (2003) empirically analyzed the positive correlation between the Chinese manufacturing sector's industrial agglomeration and economic performance [1]. He, Pan and Sun (2007) found that the Chinese manufacturing sector is highly concentrated in the Pearl River Delta, Yangtze River Delta and the Bohai Rim.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of regional growth in China have focused separately on agglomeration economies (e.g., Fan and Scott, 2003;Lu and Tao, 2009;Ke, 2010), exports and foreign direct investment (Wu, 2007;Hao and Wei, 2010;Dreger and Zhang, 2014), household amenity attractiveness (e.g., Liu and Shen, 2014), and housing supply (e.g., Wang and Zhang, 2014;Yuan and Hamori, 2014). Yet, there have not been any studies that have compared the relative importance of labor demand, labor supply and housing supply as sources of regional growth in China using multiple economic indicators as has been done for the US (Partridge and Rickman, 1999;2003;2006;Glaeser and Tobio, 2008;and Rickman and Wang, forthcoming).…”
Section: Introductionmentioning
confidence: 99%